Angulation and Distance of Superior Mesenteric Artery According to Body Mass Index on Patients Based on Computed Tomography Scan Study at Chitwan Medical College - Adhikari, Deepak; Paudyal, Sudil; Paudel, Bigyan; Paudel, Dipesh; Acharya, Ishwor (Journal of Chitwan Medical College, 2019)
Background: Superior mesenteric artery syndrome is a rare but vital cause of upper gastrointestinal obstruction which occurs when the third portion of the duodenum is trapped between aorta and superior mesenteric artery. The significant decrease of the angle and distance between the superior mesenteric artery and aorta is the etiology of Superior mesenteric artery syndrome.The study aimed to identify the angulations and distance of superior mesenteric artery from aorta and their correlation with body mass index in patients referred for contrast enhanced computed tomography of abdomen examination in Chitwan Medical College. Methods: The angle between the aorta and superior mesenteric artery was measured in arterial phase of the abdominal scan in the multiplanar reconstructed image in sagittal plane. The distance between the superior mesenteric artery and aorta was measured in axial plane at the level of 3rd part of duodenum. Results: The aortomesenteric distance was obtained to be 13.30 ± 4.75 mm and the aortomesenteric angle was obtained to be 54.7±16.91 degree for a total of 210 patients. There was a positive correlation between body mass index and aortomesenteric distance (p=0.086) and significant positive correlation between body mass index and aortomesenteric angle (p=0.122). Additionally, it showed there was significant positive correlation between aortomesenteric angle and aortomesenteric distance. Conclusions: The distance and angle between the superior mesenteric artery and the aorta correlates significantly with the body mass index which indicates that the decrease in body mass index can be used as a risk factor of superior mesenteric artery syndrome.